Time Course of Metabolomic Alterations in Cerebrospinal Fluid After Aneurysmal Subarachnoid Hemorrhage - Ho, Wing Mann; Görke, Alice S.; Glodny, Bernhard; Oberacher, Herbert; Helbok, Raimund; Thomé, Claudius; Petr, Ondra (Frontiers in Neurology, 2020)
Object The aim of this study was to investigate metabolite levels in cerebrospinal fluid (CSF) in their time-dependent course after aneurysmal subarachnoid hemorrhage (aSAH) comparing them to patients harboring unruptured intracranial aneurysms. Methods Eighty CSF samples of 16 patients were analyzed. The study population included patients undergoing endovascular/microsurgical treatment of ruptured intracranial aneurysms (n=8), which were assessed for 9 days after aSAH. Control samples were collected from the basal cisterns in elective aneurysm surgery (n=8). The CSF samples were consecutively collected with extraventricular drain (EVD) placement/intraoperatively, 6 hours later, and daily thereafter (day 1-9). The endogenous metabolites were analyzed with a targeted quantitative and quality controlled metabolomics approach using the AbsoluteIDQ®p180Kit. Differences inbetween timepoints and compared to the control group were evaluated. Results Numerous alterations of amino acid (AA) levels were detected within the first hours after bleeding. The highest mean concentrations occurred one week after aSAH. AA levels were continuously increasing over time starting 6 hours after aSAH. Taurine concentration was highest briefly after aSAH starting to decrease already after 6 hours (vs. day 1-9, p=0.02). The levels of sphingomyelins/phosphatidylcholines/lysophosphatidylcholines/mono-unsaturated fatty acid chain were highly elevated on day 0 (compared to other timepoints or controls, p<0.01) and decreased over the next several days to concentrations comparable to the control group. Carnitine concentrations were decreased after SAH (vs. day 7, p<0.01), while they recovered within the next day. The Fischer ratio of branched-chain AA to aromatic AA was lowest immediately after SAH and increased in 7 days (p<0.001). Conclusion AA levels in CSF increased overtime and often differ from patients without SAH. There was a peak concentration of structural AA within the first 6 hours after aneurysm treatment. Time-dependent alterations of CSF metabolites and compounds may elucidate pathophysiological processes after aSAH, providing potential predictors assessed non-invasively by routine lab testing.